2015
DOI: 10.1186/s13104-015-1172-2
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing preferences in rapid tranquillisation: a survey in Belgian psychiatrists and emergency physicians

Abstract: BackgroundThe pharmacotherapeutic management of agitation is a common clinical challenge. Pharmacotherapy is frequently used, the use of published guidelines is not known. The purpose of this study was twofold; to describe the prescribing patterns of psychiatrists and emergency physicians and to evaluate to which extent guidelines are used.MethodsA cross-sectional survey in the Dutch-speaking part of Belgium is carried out in 39 psychiatric hospitals, 11 psychiatric wards of a general hospital and 61 emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…It was also identified that the pharmacological management was performed in only 1.3% of the cases, and its main objective was to reduce the symptoms of agitation and aggressiveness. A Belgian study having 108 physicians working in the psychiatric emergency services found that antipsychotics are the most widely used drugs in clinical practice in situations of acute agitation, 34 which corroborates the findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…It was also identified that the pharmacological management was performed in only 1.3% of the cases, and its main objective was to reduce the symptoms of agitation and aggressiveness. A Belgian study having 108 physicians working in the psychiatric emergency services found that antipsychotics are the most widely used drugs in clinical practice in situations of acute agitation, 34 which corroborates the findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…This study demonstrates that droperidol is the most common monotherapy prescribed for the management of acute agitation in Australia. This differs from other countries, where haloperidol is the first choice for sedation of acutely agitated patients in the US, the UK, Europe and Hong Kong . This difference may be related to the limited availability of droperidol in these countries.…”
Section: Discussionmentioning
confidence: 73%
“…For example, in a recent survey, 108 psychiatrists and emergency physicians in Belgium were asked to rank their first choice drug for rapid tranquillisation of agitated patients in secluded and non-secluded settings from a list of 80 drugs [41]. In the secluded setting, clotiapine was the first drug of choice of 21.3 % of respondents, with olanzapine and droperidol being the first drug of choice of 21.3 and 14.8 % of respondents, respectively.…”
Section: Countries (Tradenames) Where Clotiapine Is Distributed Bymentioning
confidence: 99%
“…In the secluded setting, clotiapine was the first drug of choice of 21.3 % of respondents, with olanzapine and droperidol being the first drug of choice of 21.3 and 14.8 % of respondents, respectively. In the non-secluded setting, olanzapine, lorazepam and clotiapine were the first drug of choice of 22.2, 21.3 and 19.4 % of respondents, respectively [41].…”
Section: Countries (Tradenames) Where Clotiapine Is Distributed Bymentioning
confidence: 99%